FOUR NEW SPECIES OF EPHOLCIS WATERHOUSE, 1875 (COLEOPTERA: SCARABAEIDAE: MELOLONTHINAE: MAECHIDIINI) FROM THE MOLUCCAS, INDONESIA - Raden Pramesa Narakusumo; Michael Balke (BRIN Publishing (Penerbit BRIN), 2019)
Here, we provide the first record of the chafer beetle genus Epholcis Waterhouse, 1875 fromthe Moluccan Islands, Indonesia. We describe four new species: E. acutus sp. nov., E. arcuatussp. nov., E. cakalele sp. nov., and E. obiensis sp. nov. A lectotype is designated for Maechidiusmoluccanus Moser, 1920, which is redescribed and transferred to the genus Epholcis as E.moluccanus (Moser) comb. nov.